INOVASI DEBOG CRISPY SEBAGAI UPAYA MENINGKATKAN PENDAPATAN KELUARGA - Kasmiati Kasmiati; Hamdani Hamdani; Ummayatul Khumairo' (Commodity : Jurnal Perbankan dan Keuangan Islam, 2022)
In general, people have the desire to get a decent life, so they work to meet their needs. Creative home businesses are considered as an alternative solution to increase the added value which in turn can increase welfare. This research was conducted to answer the problem of how a home-based business that utilizes the potential of natural resources in Karanganyar Ngawi Village can improve the family's economy. The intended effort is in the form of innovative chips from banana stems or what is called debog crispy. This research is field research with a qualitative-descriptive approach. The main data for this study were explored through structured interviews with competent informants, namely the head of Karanganyar Village, the head of the PKK, and 13 debog crispy home-based entrepreneurs. The results of this study indicate that the debog crispy innovation home-based business plays a role in increasing family income, especially for mothers in Karanganyar Ngawi Village. From an Islamic economic perspective, this business is carried out properly and does not deviate from Shari'a, and applies the principles of monotheism, mashlahah, and justice.